Development of Measuring Technique of Start Combustion using Ion Current Measurement in a Controlled Reactivity Engine - Nuntapap, Nawee; R, Chaiya; Munsin, Ronnachart; Nilapai, Ob (Food Agricultural Sciences and Technology, 2019)
This project aims to develop a technique for measuring the start of the combustion. The principle of ion current measurement is used in the controlled reactivity engine combustion. The engine used in the test is 4-stroke diesel engine (Mitsuki Brand Model 186F). The displacement volume is 406 cc. Test fuel is diesel mixed with gasohol E85 at different ratio. The start of fuel injection can be measured by needle lift sensor, and the start of combustion can be measured by ion current sensor. Then, signals of the start of fuel injection and the start of combustion are used to fi nd the ignition delay. The engine is performed at a constant engine speed of 1,500 RPM with various engine loads of 25%, 50% and 75%. The results showed that the maximum load of the engine is obtained in case of the conventional diesel. The start of injection of blended fuels of E85 shows insignifi cant difference compared to diesel. The increase of blend increases the ignition delay.